To Work at Clinics or at Hospitals? Analysis of Family Physician Recruitment Advertising in Taiwan - Yi-Shin Cheng (International Journal of Environmental Research and Public Health, 2020)
Family physicians act as gatekeepers of the healthcare system and have an indispensable role in providing holistic care in the primary care system. While previous studies had focused on the geographic maldistribution of family physicians, the current study investigated the distribution of job opportunities for family physicians by analyzing recruitment advertisements posted in medical association journals, as an indirect way to observe the marketplace demand for physicians. We collected all the recruitment advertisements for family physicians in the twelve issues of the Taiwan Medical Journal, the official organ of the Taiwan Medical Association, in 2018. In contrast to 124 new trainees annually, 739 advertisements for family physicians were posted within the entire year. After eliminating repeated advertisements, there were 302 distinct advertisements, of which hospitals accounted for 18.9% (n = 57). The job opportunities at hospitals were offered mainly by regional hospitals (n = 26) and community hospitals (n = 29), but only two by medical centers. Family physicians in Taiwan were in great demand not only by primary care clinics but also by hospitals. The role of family physicians in hospitals is worth further study.